2022
DOI: 10.32615/ps.2021.055
|View full text |Cite
|
Sign up to set email alerts
|

Light quality, oxygenic photosynthesis and more

Abstract: Note a: See Allakhverdiev et al. (2016) for an article honoring the lifetime achievements of George C. Papageorgiou. Note b: One of us (Govindjee) is very proud to remember George Papageorgiou to be his first PhD student, whose 1968 PhD thesis in Biophysics, at the University of Illinois at Urbana-Champaign (UIUC), was extraordinarily unique, for that time; it was on 'Fluorescence induction in Chlorella pyrenoidosa and Anacystis nidulans and its relation to photophosphorylation' (available at: https://www.life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 432 publications
(439 reference statements)
0
16
0
Order By: Relevance
“…Despite the evolutionary connection between cyanobacteria and plants, the structural and kinetic differences between cyanobacteria and plants (e.g., competition for electrons due to respiration [17], phycobilisomes (PBSs) as cyanobacterial light-harvesting antennae, photoprotection mediated by Orange Carotenoid Protein (OCP), existence of Carbon Concentrating Mechanism (CCM)) prevent the use of established plantbased models for photosynthesis [3,17,18,19,20,21]. Even standard experimental methods developed for plants for non-invasive probing of photosynthesis using spectrometric techniques, such as Pulse Amplitude Modulation (PAM) fluorometry and the Saturation Pulse method (PAM-SP) [22], may require either adaptation or change in the interpretation of the measurements when applied to cyanobacteria [3,23,24]. In PAM fluorometry, a modulated light source is used to excite the chlorophyll molecules [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evolutionary connection between cyanobacteria and plants, the structural and kinetic differences between cyanobacteria and plants (e.g., competition for electrons due to respiration [17], phycobilisomes (PBSs) as cyanobacterial light-harvesting antennae, photoprotection mediated by Orange Carotenoid Protein (OCP), existence of Carbon Concentrating Mechanism (CCM)) prevent the use of established plantbased models for photosynthesis [3,17,18,19,20,21]. Even standard experimental methods developed for plants for non-invasive probing of photosynthesis using spectrometric techniques, such as Pulse Amplitude Modulation (PAM) fluorometry and the Saturation Pulse method (PAM-SP) [22], may require either adaptation or change in the interpretation of the measurements when applied to cyanobacteria [3,23,24]. In PAM fluorometry, a modulated light source is used to excite the chlorophyll molecules [22].…”
Section: Introductionmentioning
confidence: 99%
“…The emitted fluorescence is then measured, and various parameters derived from this fluorescence signal can provide insights into the efficiency of photosynthesis, the health of the photosynthetic apparatus, and other aspects of plant physiology. Compared to plants and green algae, the measured fluorescence of cyanobacteria has contributions from PSII, PSI, and detached PBS resulting in distinct fluorescence behavior [3, 24, 25, 26].…”
Section: Introductionmentioning
confidence: 99%
“…In plants and green algae, the redox state of the PQ pool controls state transitions, which modify the energy balance between PSI and PSII (Allen et al 1981, Vener et al 1997, Finazzi et al 2001, Depège et al 2003, Nawrocki et al 2016 and regulates nuclear and chloroplast gene expression (Escoubas et al 1995, Pfannschmidt et al 1999, Schönfeld et al 2004. Antenna structures are known to react to the balance of the photosystems (for a review, see Lazar et al 2022). In natural conditions with polychromatic white light, extreme oxidation or reduction of the PQ pool is unlikely, as electron transfer reactions of both photosystems function.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of light quality (spectral composition or color) on the growth and photosynthetic activity of oxygenic organisms has been attracting an extensive amount of research interest for the purpose of increasing biomass production; however, such a study of anerobic photosynthetic bacteria has been less frequent, although considerable efforts have been spent on the light-quality acclimation of bacterial niches with an emphasis on the light-harvesting antennae. For instance, it had been shown that the pigment compositions of bacterial antenna are dependent on light intensity and quality, , as well as on oxygen concentration in the presence of light. , …”
mentioning
confidence: 99%